A study investigating the impact of peer mentoring on pupils transitioning into secondary school who may be at risk of behavioural, emotional and social difficulties - Perry, Elaine (2011)
Transition to secondary school is almost always a significant period of worry and anxiety. Research has linked it to a number of negative outcomes for young people including lower self-esteem and self-concept and lower academic achievement. Previous literature suggests that peer mentoring can combat negative effects associated with transition.